Simulation of Wave and Non-Newtonian Mud Interaction using an ‎‎ISPH Based on Modified Inter-Particle Average ‎ - Kourosh Hejazi; Mohsen soltanpour; Abolfazl Aslani Kordkandi (Numerical Methods in Civil Engineering)
Fluid mud is found in ‎many areas, ‎including coastal ‎area ‎and river ‎estuaries.‎ The typical ‎characteristics of ‎overlaying waves ‎interacting with ‎muddy beds are mud ‎mass transport and ‎high wave ‎‎attenuation ‎‎(dissipation). In this ‎study, an ‎Incompressible ‎Smoothed Particle ‎Hydrodynamics‏ ‏‏‎(ISPH) ‎method has ‎been developed to ‎simulate the ‎interaction of wave ‎and non-Newtonian ‎mud. A modified ‎inter-particle ‎average technique ‎was used to solve the ‎‎discontinuity through ‎the interface. An ‎iterative method was ‎applied to update ‎viscous force and to ‎fulfill the requirement ‎of the full ‎‎incompressibility ‎of ‎the fluid. An improved ‎formulation of ‎viscous force terms, ‎new interface and ‎‎free-surface ‎treatments have been ‎presented. Some ‎hydrodynamic tests ‎were performed to ‎‎verify the model by ‎comparing the ‎simulated results with ‎‎analytical solutions. ‎Several wave-mud ‎simulations were ‎carried out to ‎investigate ‎ mass ‎transport velocities ‎and wave attenuation ‎‎in the mud layer ‎under the different ‎wave and mud ‎characteristics. To ‎validate the results, ‎the simulated results ‎were compared with ‎the laboratory ‎measurements. The ‎new modifications ‎‎improve the force ‎transferred from the ‎surface wave into the ‎fluid mud and ‎enhance the ‎‎simulated results in ‎terms of the position ‎of the particles, ‎dissipation rate, and ‎mud mass transport ‎velocity. An ‎intense ‎gradient in the mass ‎transport velocity is ‎found at the water-‎mud interface. ‎